Improving Power Quality in AC Supply Grids - Piotr Fabijański (Acta Energetica, 2015)
This paper describes a digital and actual model of the UPQC (Unified Power Quality Conditioner) integrated system for power quality improvement. The UPQC’s design and its connection to an AC supply grid, 1-phase and 3-phase alike, provide effective compensation of unwanted interferences in the waveforms of load supply voltages and non-linear load currents. This article presents an overview of topologies and control strategies. The study of the UPQC confirmed its positive impact on the power quality. The electricity parameters were significantly improved. Total harmonic distortion in supply voltage THDu decreased six-fold to 1.89%, and total harmonic distortion in load current THDi decreased more than ten-fold to 2.38% for a non-linear load (uncontrolled bridge rectifier with load L). Additionally, symmetrisation of supply voltages and reactive power compensation Q of linear load was obtained. The UPQC integrated system for power quality improvement can be used wherever high-quality and PN-EN 50160 standard – compliant electricity is required.